Mobile application development for itinerary focused automated trip planning (tourific) - Liu, Wanhua (Nanyang Technological University, 2022)
Mobile application that is travel related has become an essential tool for tourists as the applications can provide them with precise and extensive travel information conveniently. But due to the lack of a central repository, it could be challenging for them to generate travel itineraries from scratch. The primary objective of this final year project is to develop a cross-platform mobile application that is itinerary planning focused -- Tourific. Tourific is designed to be a cross-platform mobile application to eliminate the additional efforts needed to develop and maintain two different codebases to support different platforms (iOS and Android). This report documents the complete design and development process of Tourific, including the database and cloud architecture design, front-end & back-end design and development, as well as frequently made mistakes during the development.